Effect of an ankle–foot orthosis on gait kinematics and kinetics: case study of post-stroke gait using a musculoskeletal model and an orthosis model - Yamamoto, Masataka; Shimatani, Koji; Hasegawa, Masaki; Kurita, Yuichi (ROBOMECH Journal, 2019)
One of the recommended post-stroke gait rehabilitation treatments is the use of an ankle–foot orthosis. In clinical practice, it is important to adjust the torque of the ankle–foot orthosis assistance to suit each patient’s body function and gait ability. The present study aimed to investigate the effect of changing the plantar flexion resistance of the ankle–foot orthosis on the post-stroke gait kinematics and kinetics during the early stance phase using a musculoskeletal model and an ankle–foot orthosis model. The subject was a male with post-stroke left hemiplegia who could walk independently without an ankle–foot orthosis and/or cane. The subject walked at a self-selected speed under the no ankle–foot orthosis condition and three ankle–foot orthosis conditions, each with a different plantar flexion resistive torque. A motion analysis system was used to measure the following spatiotemporal parameters: gait speed, step length, cadence, and step length ratio. In addition, the ankle angle of the paretic side, ankle torque of the paretic side, and plantar flexion resistance torque of the ankle–foot orthosis were calculated using a musculoskeletal model and an ankle–foot orthosis model. The results showed that the gait speed and step length ratio of all ankle–foot orthosis conditions were improved compared with the no ankle–foot orthosis condition. In particular, the condition with the smallest torque was the most symmetric of the four walking conditions. The condition with the smallest torque also resulted in the greatest increase in the dorsiflexion angle of the paretic side at heel contact. The internal dorsiflexion torque was most increased in the ankle–foot orthosis condition with the smallest torque for this subject. The simulation of the post-stroke gait in the present study contributes to the development of more effective gait rehabilitation treatment methods using an ankle–foot orthosis.